Applying for, Operating, and Renewing a Research Experience for Undergraduates Site Program in Computational Biology - Hong Qin (Journal of Systemics, Cybernetics and Informatics)

(untitled)
We reflected on our experience in applying for, operating, and renewing a Research Experience for Undergraduates Site program in computational biology from 2016 to 2021 at a metropolitan public university, funded by the National Science Foundation of the U.S.A. Our mistakes during the application process were avoidable in retrospect. Our Interdisciplinary Computational Biology, iCompBio, REU site was a 10-week summer research program that included R and Python coding bootcamps at the beginning and short workshops on various topics interspersed throughout the program. ICompBio was in-person in 2019 and virtual in 2020 and 2021. ICompBio was fortunate to have a team of faculty mentors that were committed to undergraduate research training and recognized the importance of diversity in computational biology. Many students and faculty mentors turned the challenges in virtual REU programs into learning opportunities and had fulfilling research experiences. ICompBio participants reported learning gains higher than average in a 2020 external evaluation for virtual REU sites, particularly in the aspects of Research Self-Efficacy, Science Identity, and Life Utility. Our lessons and experiences may be helpful to other faculty and researchers that are interested in similar programs at their own institutions.